2017
DOI: 10.1002/ejic.201700199
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Influences on the Stability and Kinetics of Cp* Rhodium(III) Azide Complexes in the iClick Reaction with Electron‐Poor Alkynes

Abstract: Rhodium(III) azide half-sandwich complexes of general formula [Rh(Cp*)(N 3 )(bpy R,R )]CF 3 SO 3 with R = H, OCH 3 were prepared in three steps in an overall yield of 55-65 %. Their stability strongly depends on the 4,4′-substituent on the 2,2′-bipyridine (bpy) ligand and increases in the order COOCH 3 < H < OCH 3 . Consequently, no stable product could be isolated for the complex with the methyl ester substituent. The title compounds easily underwent cycloaddition reactions with ethyl 4,4,4-trifluoro-2-butyno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…Complex 3 upon treatment with AgSbF 6 in MeCN in dark for 24 h at r.t. afforded cationic complex 8 as yellow orange solid in 85 % yield (see Scheme ). Metal azido complexes have been used extensively as metallo‐dipolarophile in azide‐alkyne cycloaddition (AAC) reactions which afforded the respective triazolate complexes under mild reaction condition . Considerable efforts have been expended in understanding the factors that promote AAC reactions involving ruthenium(II) azido‐dipolarophile , .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex 3 upon treatment with AgSbF 6 in MeCN in dark for 24 h at r.t. afforded cationic complex 8 as yellow orange solid in 85 % yield (see Scheme ). Metal azido complexes have been used extensively as metallo‐dipolarophile in azide‐alkyne cycloaddition (AAC) reactions which afforded the respective triazolate complexes under mild reaction condition . Considerable efforts have been expended in understanding the factors that promote AAC reactions involving ruthenium(II) azido‐dipolarophile , .…”
Section: Resultsmentioning
confidence: 99%
“…A copper(I) catalyzed click reaction involving organic azides and alkynes to afford 1,4‐disubstituted 1,2,3‐triazoles selectively is known since the pioneering work of Fokin, Sharpless and Meldal published in 2002 , . Such reactions involving metal azide/alkyne known as early as 1974, metal alkyne/organic azide, metal azide/metal alkyne, popularly known as inorganic click (iclick) reaction, are the emerging reactions for metal triazolate complexes that could contain either a metal‐nitrogen bond or a metal‐carbon bond depending upon the reaction partners . Continuing our interests in understanding the reactions of guanidinatometal azido complexes with alkynes and factors that dictate the stereochemistry of o ‐substituted N , N′ , N′′ ‐triarylguanidinato ligand in the resulting triazolate complexes,, we report herein the reactions of 5 with diethylacetylenedicarboxylate (DEAD) and bis(diphenylphosphanyl)acetylene (DPPA) which afforded two distinct products, namely 9 and 10 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the standard copper-catalyzed azide–alkyne cycloaddition (CuAAC), no catalyst is required for this reaction, and it smoothly and without a trace leads to robust metal triazolato compounds. Since then, the scope of the iClick reaction has been significantly expanded , and now covers a good part of the d-block elements (Scheme B), from group VI (Mo and W) to group XI (Au). , Initial studies have also revealed promising biological activity, for example, on cancer cells. ,, In order to fully explore the promise of the iClick reaction for biological labeling with metal complexes, however, very fast kinetics are required, as conjugation reactions have to proceed on a timescale faster than the biological process of interest. In the initial work of Veige, a rate constant of 7.6 × 10 –3 M –1 s –1 was reported for the reaction of [Au­(N 3 )­(PPh 3 )] with [Au­(CCC 6 H 4 R)­(PPh 3 )] .…”
Section: Introductionmentioning
confidence: 99%
“…In the initial work of Veige, a rate constant of 7.6 × 10 –3 M –1 s –1 was reported for the reaction of [Au­(N 3 )­(PPh 3 )] with [Au­(CCC 6 H 4 R)­(PPh 3 )] . In square-planar Pd­(II) and Pt­(II) azido complexes with a semithiocarbazone N^N^S coligand and octahedral Mo­(II)/W­(II) and Rh­(III)­Cp* compounds, , we determined second-order rate constants that were, in the most promising cases, about two orders of magnitude higher than those of the initial iClick reaction. Still, the reaction was restricted to internal alkynes RCCR′ with strongly electron-withdrawing substituents such as R = CF 3 , R′ = COOEt, or R = R′ = COOCH 3 .…”
Section: Introductionmentioning
confidence: 99%
“… 4 6 A range of d-block azido complexes, including those of Mn( i ), 7 , 8 Fe( iii ), 9 Pd( ii ), 10 Pt( ii ), 10 15 Rh( iii ) 16 and Au( i ), 17 have been reported to undergo copper-free 1,3-dipolar cycloaddition or “click” reactions with carbon–carbon and carbon-heteroatom functional groups such as alkynes, isocyanides, isonitriles, nitriles, carbon disulphides and isothiocyanates. Electron-deficient alkynes such as dimethyl acetylenedicarboxylate (DMAD) and diethyl acetylenedicarboxylate (DEACD) are relatively reactive: Mo( ii ), 16 , 18 Co( iii ), 19 Fe( iii ) 19 , 20 Ru( ii ), 20 25 Pd( ii ) 26 28 and Ta 29 azido complexes all react with DMAD. Strain-promoted azide–alkyne cycloadditions (SPAAC) 30 , 31 are also an effective method for derivatising azido complexes.…”
Section: Introductionmentioning
confidence: 99%